El homo sexualis latinoamericano de la época tardíomoderna La narrativa de Jaime Bayly - Szymoniak, Ewelina (Romanica Silesiana)
The Latin American Homo Sexualis of High Modernity. Jaime Bayly’s Narrative Fiction Jaime Bayly is one of the most controversial Hispanic-American writers of recent times. Both his provocative media image and his writings — which supposedly reffer to his personal experience — focus on gay themes. The aim of the present article is to show, by way of the work of literary scholars who engage in queer theory and sociologists who examine questions of sexuality, how certain changes in the sexual dimension of human life typical of societies of so-called high modernity (although with marked influences from Latin American culture), are reflected in th Peruvian’s writings. Situating Bayly’s novels in a broader literary and social context, the article attempts to shed light on the cultural construction of gender and sexuality. Key words: (homo)sexuality, hypermasculinity, hegemony, identity.